2019
DOI: 10.2478/cait-2019-0037
|View full text |Cite
|
Sign up to set email alerts
|

Mission Critical Messaging Using Multi-Access Edge Computing

Abstract: 5th Generation (5G) mobile system is expected to support the requirements of mission critical communications for ultra reliability and availability, and very low latency. With the development of messaging and data transfer in mobile networks, mission critical communication users see more and more potential in data communications. In this paper, we explore the capabilities of Multi-access Edge Computing (MEC) that appears to be a key 5G component, to provide short messaging service at the network edge. The prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…By centralizing certain functionalities, cloud computing enables on-demand resource sharing and it empowers applications with elasticity and scalability at low cost [16], [17]. In [18], it is shown that the cloud-based heterogeneous access network architecture exceeds the distributed architecture in terms of throughput performance. Network programmability opens the network capabilities and services for third party developers, enabling attractive applications and personalized user experience [19].…”
Section: Related Workmentioning
confidence: 99%
“…By centralizing certain functionalities, cloud computing enables on-demand resource sharing and it empowers applications with elasticity and scalability at low cost [16], [17]. In [18], it is shown that the cloud-based heterogeneous access network architecture exceeds the distributed architecture in terms of throughput performance. Network programmability opens the network capabilities and services for third party developers, enabling attractive applications and personalized user experience [19].…”
Section: Related Workmentioning
confidence: 99%
“…MEC can address challenges imposed by mission critical and healthcare communications as it enables building of vertical segments and service deployment at network edge. Moving the cloud intelligence in the vicinity of end users reduces latency, optimizes network resource utilization, and improves security [6], [7].…”
Section: Introductionmentioning
confidence: 99%